2008
DOI: 10.1063/1.2890714
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field induced ferroelectric loop in Bi0.75Sr0.25FeO3−δ

Abstract: Magnetic field induced ferroelectric hysteresis loop observed in Bi 0.75 Sr 0.25 FeO 3-delta is of prime importance. The coexistence of antiferromagnetism and weak ferromagnetism is responsible for the original magnetoelastic and magnetoferroelectric properties. Upon external magnetic field application, the existence of a magnetostrictive effect supports a structural transition towards a homogeneous antiferromagnetic and ferroelectric phase. The magnetic field induced polarization is among the highest reported… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 31 publications
2
31
0
1
Order By: Relevance
“…It is due to random doping of Ga ions in rhombohedral planes containing Fe ions and distribution of magnetic exchange interactions. B. Kundys et al 27 attributed similar magnetic field induced NDR effect in Bi 0.75 Sr 0.25 FeO 3 system to coexistence of antiferromagnetic and weak ferromagnetic interactions. In Ga doped hematite system, we noted a good signature of ferroelectricity in the nearby composition (α-Fe 1.6 Ga 0.4 O 3 ) and prepared by mechanical alloying.…”
Section: Summary Of the Results And Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is due to random doping of Ga ions in rhombohedral planes containing Fe ions and distribution of magnetic exchange interactions. B. Kundys et al 27 attributed similar magnetic field induced NDR effect in Bi 0.75 Sr 0.25 FeO 3 system to coexistence of antiferromagnetic and weak ferromagnetic interactions. In Ga doped hematite system, we noted a good signature of ferroelectricity in the nearby composition (α-Fe 1.6 Ga 0.4 O 3 ) and prepared by mechanical alloying.…”
Section: Summary Of the Results And Discussionmentioning
confidence: 94%
“…In NDR regime, the I-V curve showed non-ohmic character where current decreases with increase of voltage to achieve a current valley at voltage V m . In the high voltage ohmic regime (HOR) at V > V m , the current once again increases with the increase of voltage up to 10 V. The NDR effect is useful for applying materials in spintronics devices, [26][27][28][29] especially in memory and switching devices. 30,31 We have shown in Fig.…”
Section: B I-v Curves Measurement In the Presence Of Magnetic Field mentioning
confidence: 99%
“…16 Interestingly, divalent cation (A) substituted Bi 0.7 A 0.3 FeO 3 (A = Ca, Sr, Pb, and Ba) also exhibits enhanced magnetization 17 and the recent observation of magnetic-field induced ferroelectric hysteresis loop in Bi 0.75 Sr 0.25 FeO 3-δ makes it more attractive for practical applications. 18 Although the temperature dependence of structural and magnetic order parameters of BiFeO 3 has been studied by Fischer et al long ago 19 , the magnetic measurements over a wide range of temperature (10 K -700 K) as well as magnetoelectric coupling in Bi 0.7 A 0.3 FeO 3 have not been reported and these are the driving factors for the work reported here. with X-ray diffraction (XRD) experiment (Philips X' pert Pro) using Cu Kα radiation.…”
Section: Introductionmentioning
confidence: 82%
“…It has to be noted that, similarly, magnetic field induced ferroelectric loop has recently been found in Sr substituted BiFeO 3 accompanied with no magnetocapacitance effect in this compound. 28 In conclusion, a quasistatic technique has been used to investigate ferroelectric properties of a single crystal of MnWO 4 . It was shown that the sample is indeed ferroelectric and that the shape of its ferroelectric loop strongly depends on both temperature and magnetic field.…”
mentioning
confidence: 99%